The Influence of Mineral Nutrition on the Productivity of Spring Rape - I. Lupova, Ekaterina; V. Vinogradov, Dmitry; V. Evsenina , Marina; S. Pityurina, Irina (KnE Life Sciences, 2021)
This article presents data on the influence of mineral nutrition on the productivity of spring bird rape varieties in the conditions of the non-chernozem zone of Russia. The experiments were carried out on agro-gray loamy soils of the experimental agrotechnological station of the Federal State Budgetary Educational Institution of Higher Education “Ryazan State Agrotechnological University” (FSBEI HE RSATU) in the Ryazan Region in 2016-2018. A level of mineral nutrition for spring bird rape was calculated asN180P100K100. Based on this, the options for mineral nutrition in research were established. According to the results of the experiments, the duration of the growing season of spring bird rape varieties was established: 73-91 days.An increase in nitrogen to 150 kg of the active substance turned out to be less effective, as the yield increased slightly or remained at the level of N90P50K50. The use of phosphoruspotassium fertilizers did not contribute to the creation of such a nutritional regime that would increase seed productivity. An increase in the nitrogen nutrition of the plants led to increased protein content anddecreased oil content in seeds. This trend was observed in all varieties of spring bird rape. The average oil content was 38.5-45.5% and the average protein contentwas 18.0-24.7%, depending on the variety and the level of mineral nutrition. On average, the highest oil content was shown by varieties Lipchanka (44.1%) and Kulta (42.6%). Keywords: agro-gray soil, level of mineral nutrition, oil content, productivity, spring bird rape, variety